Legislative Measures to Prevent Torture and Brutality – Constitution of India and Other Statutory Provisions: Examining the prevalence of physical torture and the legal framework in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Physical torture of the prisoners in police custody has been very unavoidable for a very long while in India. The prisoners in police guardianship in India incorporate undertrials (people who have been accused of perpetrating wrongdoings) just as political detainees. The truth is, neither of these two sorts of prisoners is saved from physical torture delivered by the police in their own guardianship. A quick survey of severity in police authority in India shows that different types of physical tor-tures are done by the police, including assault.